Gambaran Kesiapan Mahasiswa Tingkat Akhir dalam Menghadapi Profesi Ners di Universitas Jenderal Soedirman Saat Pandemi Covid-19 - Laela Fajrin Ramadhani; Eva Rahayu; Arif Imam Hidayat (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Background. Covid-19 pandemic has an affect on changing the learning methods of Nurse Internship Program at Jenderal Soedirman University. The Nurse Internship Program is carried out by limiting students who practice in hospitals or clinics and combining learning online and offline. With these changes, it may affect student’s readiness to continue nurse profession. Methods. This study used quantitative research design. Sampling using total sampling technique with 90 people as sample from class 2016 and class 2017. Data analysis used univariate test. Results. The majority of respondent have a good level of readiness (60,0%). Most of the respondent were 21 years old. The majority of responden were women as many as 80 people (88,9%). And most of the respondent came from class 2017 as many as 76 people (84,4%). From age range of respondents, 21 years old have a better readiness (64,3%) than other ages. Respondent with male gender have better readiness (70,0%) than women (58,8%). Class 2016 has better readiness than class 2017 (59,2%). Conclusion. The majority of the respondents have a good readiness category (60,0%).